The Technical Teacher Training Institutes in India-Some Future Perspectives - Ramkrishan Sastri, C. (Journal of Engineering Education Transformations, 1997)
The four Technical Training Institutes in India at Bhopal, Calcutta, Chandigarh and Madras have been serving the cause of Technician Education in India for the past 30 years quite admirably providing the much needed resource and support services. They have introduced several innovations in the system which have come to stay and which are now much sought after in other systems as well. Yet, the expectations from these institutions far exceeds the achievements and the future scenario is likely to consist of greater challenge and newer thrusts. This article attempts briefly to list out some of these future roles and responsibilities of these institutions in the initial years of the 21st century.